The benefits of using bio-bricks in affordable housing projects in Perak / Azizul Rahman Mohammad @ Nadzri - Mohammad @ Nadzri, Azizul Rahman (2022)
In this study, researcher is investigating the benefits of Granite Dust Bio-Bricks. The Granite Dust Bio-Bricks were compared to traditional Clay bricks. The goal of the survey was to determine the level of sustainability awareness among Malaysian construction industry players in Perak, state stakeholders and the actual on-the-ground experience of employing Granite Dust Bio-Bricks in affordable housing projects. This is to discover important facts about Granite Dust Bio-Brick for the building industry and the impact on the environment and living comfort in Perak's. In this study, the things that are tried to be highlighted are the challenges, level of awareness and determining factors to industry players in using bio-brick in the construction of affordable housing. Granite Dust Bio-Brick implementation steps in Perak are formulated using a greater grasp of the challenge. Data will be gathered through the internet, public libraries, books, journals, green buildings and Bio Brick products. A questionnaire will be used as a medium to obtain primary data. The intended respondent was given questionnaires to fill out. The information gathered was examined using the appropriate methodologies. The raw data collected was analyzed and reported. The methodology used in this study will comprise the standard frequencies and cross tabulation to see the link between the independent and dependent variables. Researchers using quantitative research strategies to find links and look for interactions between variables. Quantitative research means exploring relationships between variables in order to verify theories that are based on objective values.